Effect of Si and Al on microstructure-property-relationship of Q&P-steels during galvannealing. Issue 2 (22nd January 2021) - Wallner, M.; Schneider, R.; Steineder, K.; Sommitsch, C.
Abstract : The influence of a thermal-treatment simulating a galvannealing-process (GA) on the microstructure of a 0.2C–4Mn–1.5Si and 0.2C–4Mn–1.5Al (in wt-%) medium-Mn-Q&P-steel was investigated in detail using dilatometry. After Q&P-process, the retained austenite (RA) fraction is higher and mechanical properties are superior for the Si-concept. Owing to galvannealing, strength decreases substantial for both concepts. For the Si-concept however, RA starts to decompose into pearlite upon galvannealing temperatures of 520°C, leading to a significant decrease in elongation. For the Al-concept, the RA-fraction remains constant up to 560°C, which even results in increased elongations values compared to the galvannealed Si concept. This contribution shows that Al as an alloy-element in Q&P-steel is more suitable for RA stabilisation at higher temperature than Si.